The Role of Cultural Codes in the Interpretation of Folklore Texts - Sharipova Malikakhon Kahramon kizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
Abstract: Cultural codes serve as fundamental semiotic mechanisms that encode and transmit national worldview, values, and collective memory within folklore texts. This study explores the role of these codes in facilitating deeper interpretation of folklore, drawing on Yuri Lotman’s theory of cultural semiotics and applying it to both universal and specifically Uzbek folkloric traditions. Through semiotic analysis, the research demonstrates how cultural codes—such as zoomorphic, phytomorphic, spatial, and mythological symbols—function as interpretive keys that unlock hidden layers of meaning in folklore narratives, proverbs, and epics. Particular attention is given to Uzbek folklore, including the epic Alpomish and traditional folk tales, where symbols like the sacred horse, divine birth motifs, and tripartite cosmic structures embody ethnocultural identity. The findings reveal that cultural codes not only preserve cultural heritage amid globalization but also enable cross-cultural dialogue by revealing shared human archetypes while highlighting unique national mentalities. This interdisciplinary approach bridges linguistics, semiotics, and folkloristics, underscoring the enduring relevance of folklore as a dynamic repository of cultural information. The study contributes to contemporary linguoculturology by emphasizing the necessity of decoding these signs for accurate textual interpretation and cultural preservation.